لفظ الجبار في القرآن الكريم: دراسة موضوعية: Lafaz al-Jabbār in the Qur'an: A Thematic Study - Al-Deek, Muhammad Youssef; Ayyash, Iman Mutaib (البصيرة: مجلة الدراسات الإسلامية, 2024)
This research highlights the word al-Jabbār in the Qur'an, with the aim of defining the term al-Qur'an based on the definition of etymology and terminology, the meaning of its derivation in the context of the Qur'an, and the implications of the nature of al-Jabbar. This research uses an inductive approach in exploring the word al-Jabbār and a descriptive and deductive approach by referring to various relevant interpretations and references and exploring the meaning of al-Jabbār in the context of the verses of the Al-Qur'an. The main finding of this research is that the origin of the linguistic use of the word al-Jabbār revolves around power, greatness, and establishing something by force. The meaning of al-Jabbār in the context of the Qur'an appears in the sense of a person in power, a person who oppresses unjustly, and a person who is arrogant in following the truth.